Bronchoscopic visualization of a cavity in entirety: an unusual finding. Issue 7 (31st August 2020) - Mishra, Deebya Raj; Bhatta, Narendra; Acharya, Achyut Bhakta; Verma, Avatar; Shahi, Rejina; Shah, Niharika
Key message: It is unusual to be able to visualize an entire cavity with such clarity. Abstract : It is unusual to be able to visualize an entire cavity with such clarity.